Model of Individual Purchase Intention Determinants for Environmentally Friendly Products - Sherly Novia; Mirza (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study examines individuals’ purchase intentions toward environmentally friendly products, with the research object being Royco products from Unilever. The population used in this study consists of residents of DKI Jakarta who use Royco products from Unilever. The sample was collected using probability sampling with the simple random sampling method. The research framework is based on the Theory of Planned Behavior (TPB), which involves the variables of attitude, subjective norm, and perceived behavioral control. The study also includes additional variables, namely environmental knowledge, environmental awareness, and willingness to pay, to explore the main factors influencing consumers’ purchase intentions. Data analysis was conducted using the Structural Equation Modeling (SEM) method.